The identification of directed technical change revisited - Marianne Saam (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Technical change that augments capital and labor input in a non-neutral way plays an important role in explaining the relation between growth and other macroeconomic outcomes. Previous research has shown that restricting technical change to be neutral leads to overestimating the elasticity of substitution between capital and labor. I extend this line of analysis to misspecification of the functional form. Evidence from Monte Carlo simulations shows that the problem of biased estimates of the direction of technical change is relevant in the estimation of aggregate CES and translog production functions. In particular, I find examples where true technical change is neutral and estimated technical change is strongly directed towards one factor.
urn:nbn:de:bsz:180-madoc-375285
Keywords: C15; O30; O47; 330; directed technical change; estimation of production functions; CES functions; translog functions